Epidemiological assessment of trends and health inequalities in rates of Group C and G Streptococcal bacteraemia in England, 2015 to 2022 - Mr Jamie Thomas Rudman; Dr Juliana Coelho; Ms Karen Broughton; Dr Christopher Jones; Dr Mariyam Mirfenderesky; Dr Colin Brown; Dr Theresa Lamagni; Ms Rebecca Guy (International Journal of Infectious Diseases)
Introduction: The epidemiology of Group C and Group G Streptococcal bloodstream infections (GCS and GGS respectively) in England has not previously been investigated in detail. Considering longitudinal increases in these pathogens, we assessed trends and health inequalities of GCS and GGS bacteraemia in England to support and prioritise development of appropriate healthcare and public health interventions. Methods: GCS and GGS bacteraemia data between 01/01/2015 and 31/12/2022 for England were extracted from UKHSA's national laboratory reporting database and reference laboratory. Data were augmented through linkage to Office for National Statistics and Hospital Episode Statistics to capture socioeconomic deprivation score (index of multiple-deprivation, IMD) based on residential location, and ethnicity. Infection rates by ethnicity and IMD were direct age-standardised. Results: Between 2015 and 2022, 11,275 GCS (range 932-1693 per-year) and 10,068 GGS (range 1070-1411) were reported in England. For GCS, the median age was 77y and 54.7% (n=6164) of cases were female, and for GGS, the median age was 79y with 52.3% female (n=5265).Annual rates of GCS increased 71% (1.7 to 2.9/100,000 population) and GGS 12% (2.0 to 2.2) between 2015 and 2022, both peaking in 2019 (3.0 and 2.5 respectively). North East England had the highest annual rates of GCS (up to 9.0/100,000 per-year); up to 2.4 times higher than the London region after age-adjustment (3.7 vs 9.0 per 100,000 in 2019, and 2.9 vs 7.0 per 100,000 in 2022).There was a disproportionate burden of GCS in patients in the most-deprived IMD-quintile of the population in England (23.7% of total; n=2677), with the least-deprived IMD-quintile comprising the smallest contribution to the total (16.5%; n=1864). Age-adjusted annual rates in the most-deprived areas were double those in the least-deprived (4.3 vs 2.3/100,000 in 2022). For GGS there was a disproportionate burden in the 40%-60% most-deprived IMD-quintile (21.4% of total; n=2152); after age-standardisation, rates were highest in the most-deprived and lowest in the least-deprived IMD-quintiles (3.4 vs 1.9/100,000 in 2022).In 2022, 95.1% of GCS (n=1,516) and 94.9% of GGS (n=1,144) cases respectively were from patients of ‘White’ ethnicity with ‘Black’, ‘Asian’, ‘Mixed’, and ‘Other’ ethnicities comprising <2% of total GCS and GGS across all years. After age-standardisation, patients with a GCS were twice as likely to be of ‘White’ ethnicity (3.1/100,000) compared to ‘Black’ (1.5) or ‘Asian’ (1.3). Discussion: This work reports the trends and demographic differences amongst patients with reported GCS or GGS bacteraemia with variation by ethnicity and IMD and offers insights into possible geographical and other demographic heterogeneities in the burden of GCS and GGS bacteraemia in England. Conclusion: This is the first national study on GCS and GGS in England. This work supports UKHSA's priority of developing awareness of health inequalities for better targeting of health interventions.